FUNCTIONAL OUTCOME OF PATIENTS WITH CHRONIC PLANTAR FASCIITIS TREATED BY LOCAL INJECTION OF AUTOLOGOUS PLATELET-RICH PLASMA - RAJESH KUMAR KANOJI; PRADEEP KUMAR SUTHAR; HIMANSHU (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of the study are as follows: To assess functional outcome of patients with chronic plantar fasciitis (PF) treated by autologous injection of platelet-rich plasma (PRP). (1) To know the side effects, if any, in these patients. Methods: This was a prospective study conducted in the Department of orthopedics of a tertiary care medical college. Forty patients having chronic PF were included in this study on the basis of a predefined inclusion and exclusion criteria. Autologous PRP was injected in plantar fascia at the point of maximum tenderness. Patients were followed up for 3 months. Intensity of pain and functional outcome was assessed using the visual analog score (VAS) score and American Orthopedic Foot and Ankle Score (AOFAS) score. For statistical purposes, p<0.05 was taken as significant. Results: There were 14 (35.00%) males and 26 (65.00%) females with a M: F ratio of 1:1.85. The mean age of male and female patients was found to be 43.82±9.98 years and 41.68±10.12 years, respectively. Majority of the patients (65%) were overweight whereas 6 (15%) patients were obese and 8 (20%) patients were having a normal healthy body mass index. The mean duration of symptoms was found to be 10.67±3.89 months. The mean VAS score at the time of final follow-up was significantly less (0.96±0.46) as compared to pre-injection VAS score (7.20±1.38) whereas the AOFAS score at the time of final follow-up (91.9±6.68) significantly improved as compared to pre-injection AOFAS score (38.96±8.78). There were no major side effects in any of the studied cases. Conclusion: Local injection of autologous PRP appears to be an effective treatment for chronic PF in terms of reduction of pain and functional improvement with no significant side effects.